alittlebitofcalculus-pdf-january2011-111112001007-phpapp01

3 limit step now we can take the limit as h 0 h l imit

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: + a n-- 1 ) x→a Substitute for x = a to get na n--1 66 estern wa Wester n w ay : f ’ (a) = ( a) L i m i t ( a + δ x ) n -- a n δ x → 0 ( a + δ x ) -- a f(x) − f(a) (a+ δ x) n -- a n = x−a ( a+ δ x)-- a In the numerator : (a+ δ x) n = an (1+ δ x )n a δ x ) n 1] n n : So: (a + δ x) -- a = a n [ (1 + a -- VERAGE step 1. AVERAGE step : ( from the right) In the denominator : (a+ δ x) -- a = δ x So: : (a+ δ x) n -- a n (a + δ x) -- a = n a [ ( 1 + δ x )n -- 1 ] a δx 2. TENDS TO step : expanding by the Binominal Theorem : a n [ ( 1 + n δ x + n( n -- 1) [ δ x ] 2 + . . . = a a 2! δx terms with higher powers of δ x ) -- 1] The +1 and --1 will cancel out. We are left with : a n [ n δ x + n( n -- 1) [ δ x ] 2 + . . . = a a 2! δx terms with higher powers of δ x ] / Since δ x → 0 but δx = 0 we may simplify the terms with δ x to get : n( n -- 1) δ x nn = a [ -- + 2! [ a2 ] + . . . terms with higher powers of δ x ] a L 3. LIMIT step : now take the LIMIT as δ x → 0 . δ ximit0 δ x = 0, → L imit δ x = 0 and L imit (terms with higher powers of δ x) = 0. δx → 0 δ x → 0 a2 n We are left with an -- = n a n--1 . a nn L imit (a+ δ x) -- a = n a n--1 δ x → 0 (a+ δ x)-- a (from the right) 67 In calculating f ’(a) when we wrote L imit we meant L imit+ , i.e. from the right. right x→a x→a We could have taken L imit , i.e. from the left . l eft x → a-n n (a -- δ x) -- a left ( from the lef t ) l ef ? ( a-- δ x ) -- a i.e. what is δL imit0 (a -- δ x)n -- an ? ( from the lef t ) left l ef x→ -- δ x IMPORTANT: notice the -- δ x in the denominator when approaching the instant a from the left : l eft x → a -- = a -- δ x as δ x → 0 a nd ( a -- δ x) -- a = -- δ x. What is δL imit0 x→ Now, r ather than c hoosing the par ticular instant a , we may w ant to i nstant find the INSTANTANEOUS RATE OF CHANGE of the function f(x) = x n a t any instant x . I n general, if we let x be any instant o ver which the i nstant instant function is WELL- BEHAVED (SINGLE...
View Full Document

This note was uploaded on 11/29/2012 for the course PHYSICS 105 taught by Professor Tamerdoğan during the Fall '09 term at Middle East Technical University.

Ask a homework question - tutors are online